Multi-Agent architecture towards the intelligent strategical algorithm for the representation and retrieval of tacit knowledge from healthcare distributed repositories - Hashmi, Zafar Iqbal; Adwan, Somaia; Hashmi, Faisal (2006)
Knowledge is deemed a key asset in today’s knowledge enriched society and such a ‘Knowledge Age’ has fuelled Knowledge Management discipline to address many complex problem issues pertaining to knowledge creation, procurement, representation, retrieval,capitalization, etc. Knowledge is categorized in many forms and one of the complex forms of knowledge is known as “Tacit Knowledge” that put forwards many challenges for acquisition and retrieval, in particular,from distributed repositories. We will present, in this paper, a novel strategical algorithm implemented with multi-agent architecture for the retrieval,of tacit knowledge with incorporation of ‘Ontology’ and ‘Query Optimization’,from distributed healthcare repositories.